The Impact of ESG Performance and Financial Constraint on Tax Avoidance: Evidence from ASEAN 5 - Anggelia Syahputri (Jurnal Dinamika Akuntansi, 2025)
Purposes: This study examines the relationship between ESG performance, financial constraints, and corporate tax avoidance. It investigates whether ESG performance reduces tax avoidance by promoting socially responsible practices and whether financial constraints lead to increased tax avoidance as a strategy to generate internal funds. Specifically, it seeks to assess how ESG practices and financial constraints influence tax avoidance behavior among publicly listed firms in ASEAN countries. Various determinants of tax avoidance have been identified in the literature; however, ESG performance and financial constraints have received less attention in association with tax avoidance from a regional perspective in a group of countries with similar yet diverse institutional contexts, such as ASEAN. It offers new insights into these relationships in a multi-country, emerging market setting. Methods: Using an unbalanced panel dataset of 242 publicly listed companies in ASEAN-5 over the 2019–2023 period with generalized least squares (GLS) regression. Findings: ESG performance is negatively associated with tax avoidance, as evidenced by higher Effective Tax Rate (ETR). Additionally, firms facing financial constraints exhibit a positive relation- ship with tax avoidance, leading to lower ETR. Financially constrained companies are hindered in accessing external funds, thus pursuing aggressive tax planning strategies to generate additional internal funds. Novelty: This study contributes to the literature by extending the understanding of tax avoidance behavior in emerging markets and at a regional level. It provides empirical evidence from the ASEAN market, which has been underrepresented in prior studies.